2013
DOI: 10.1186/2196-1042-14-26
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crown-root angle on stress distribution in the maxillary central incisors’ PDL during application of intrusive and retraction forces: a three-dimensional finite element analysis

Abstract: BackgroundDifferent crown-root angulations of maxillary central incisors can be assumed as a potential reason for many underscored outcomes of orthodontic treatments. The aim of this study was to determine the effects of the different crown-root angles on stress distributions in the maxillary central incisor’s periodontal ligament (PDL) during application of intrusive and retraction forces using a 3D finite element method.MethodsTwo models of a maxillary central incisor were constructed using ANSYS software: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…1 The overall tooth length (crown height and root length) determines the orthodontic force that can be transmitted during orthodontic treatment, and it is involved in the pattern of tooth movement. [2][3][4] Furthermore, the identification of the root length at the time of orthodontic diagnosis and treatment is essential. 5 Both environmental and genetic factors can lead to dental variation.…”
Section: Introductionmentioning
confidence: 99%
“…1 The overall tooth length (crown height and root length) determines the orthodontic force that can be transmitted during orthodontic treatment, and it is involved in the pattern of tooth movement. [2][3][4] Furthermore, the identification of the root length at the time of orthodontic diagnosis and treatment is essential. 5 Both environmental and genetic factors can lead to dental variation.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,6,21 In this study, the entire PDL was collected for molecular analysis for 2 major reasons: (1) because GCF continuously circulates in the PDL, there is no clear-cut difference in the assessment of cytokines in GCF from the pressure or tension areas 21 ; and (2) regardless of the type of tooth movement, 22-25 irregular patterns of stress occur because of uneven strain distribution in the PDL, making it difficult to precisely define the sites of tension and pressure. 25 The Th1/Th2/Th17 cytokines have already been associated with periodontal T-cell responses under conditions of periodontal disease and bone cell regulation. 26 This study demonstrated for the first time the kinetics of Th1 (TNF-a, IFN-g), Th2 (IL-2, IL-4, IL-6, IL-10), and Th17 (IL-17A) cytokine release in human PDL and GCF after mechanical stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Without PDL, soft tissues, and remodeling within the model, the teeth are essentially ankylosed within the dentoalveolar bone. While the simulation does not accurately predict the dental effects [ 21 23 ], it does, however, demonstrate the skeletal effects, which is of primary concern when it comes to growth modification procedures like maxillary protraction. This study is valid in comparing how location and vector of force alters the skeletal effects.…”
Section: Discussionmentioning
confidence: 99%